Novel 4-Volt Class Ultra Fine Lithiated Transition Metal Oxides For Power Sources - K., Mumtaj Begam (2005)
In today's rechargeable lithium-ion batteries (both PLI and LLI technologies), the candidate cathode material, lithium cobalt oxide(LiCoO2) has the following disadvantages: cobalt (Co) is too expensive (particularly for large scale applications) and environmentally unfriendly due to the presence of toxic cobalt. These limitations make LiCoO2 unsuitable for future lithium-ion batteries.